2008
DOI: 10.1111/j.1365-2982.2008.01122.x
|View full text |Cite
|
Sign up to set email alerts
|

Oesophageal afferent pathway sensitivity in non‐erosive reflux disease

Abstract: Patients with non-erosive reflux disease (NERD) report symptoms which commonly fail to improve on conventional antireflux therapies. Oesophageal visceral hyperalgaesia may contribute to symptom generation in NERD and we explore this hypothesis using oesophageal evoked potentials. Fifteen endoscopically confirmed NERD patients (four female, 29-56 years) plus 15 matched healthy volunteers (four female, 23-56 years) were studied. All patients had oesophageal manometry/24-h pH monitoring and all subjects underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 32 publications
1
31
0
2
Order By: Relevance
“…In this study, two patients reported chest pain during meal period, although endoscopic removal of the capsule was not necessary. The proposed mechanism to chest pain in these patients probably is related to abnormalities in central or peripheral visceral nociception, in particular, decreased threshold in generation or perception of symptoms (9) . Similar to other authors (10,31) patients in this study did not complain of pharyngeal discomfort or interference in their daily activities.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, two patients reported chest pain during meal period, although endoscopic removal of the capsule was not necessary. The proposed mechanism to chest pain in these patients probably is related to abnormalities in central or peripheral visceral nociception, in particular, decreased threshold in generation or perception of symptoms (9) . Similar to other authors (10,31) patients in this study did not complain of pharyngeal discomfort or interference in their daily activities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the same symptom can be produced by a physiological intraesophageal acid exposure [7]. Increased esophageal sensitivity to esophageal distension or stimulation [8,9,10,11], non-acid reflux [12, 13], and esophageal motor abnormalities [14] are suggested to play a role in the genesis of heartburn. Based on ambulatory esophageal pH monitoring, patients with no evidence of esophagitis on endoscopy can be subdivided as having excessive or normal esophageal acid exposure time.…”
Section: Discussionmentioning
confidence: 99%
“…27 In addition, a previous study found that increased sensitivity to esophageal pain was present in a subset of PPI-resistant NERD patients. 28 Therefore, reflux perception and increased sensitivity to pain may be associated with different responses to PPI therapy in ERD vs NERD patients. Our study revealed a significant association between BMI and response to PPI.…”
Section: Discussionmentioning
confidence: 99%